The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/0100-2945-377/13
|View full text |Cite
|
Sign up to set email alerts
|

Sistema geovitícola para a produção de uvas para vinho na região do Circuito das Frutas-SP

Abstract: Rev. Bras. Frutic., Jaboticabal -SP, v. 36, n. resumo -Nos últimos anos, tem-se observado aumento na produção de uvas destinadas à elaboração de vinhos na região do Circuito das Frutas, Estado de São Paulo, promovido principalmente pelo turismo rural. O objetivo deste trabalho foi caracterizar o potencial climático dessa região para produção de uvas para vinho, utilizando o Sistema de Classificação Climática Multicritérios Geovitícola, baseado nos índices biometeorológicos: heliotérmico, de frio noturno e de s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…In São Paulo state, Marin et al (2008) found climate similarities among the wine producing regions of Bento Gonçalves in Rio Grande do Sul, Beli Kriz in Slovenia, Tarragona in Spain, Ajjacio, Bastia, Braga, Bordeaux, Carcassone, Pau and Toulouse in France, Pune, in India, Ravenna in Italy, Kofu in Japan, Napier in New Zealand, Bangkok and Chiangmai in Thailand and Las Brujas in Uruguai. Bardin-Camparotto et al (2014), by using the CCM system to characterize climate potential for grape production in the São Paulo -Circuito das Frutas region, concluded that wine producing climate of the HI class for the summer harvest were "warm", "temperate warm", "temperate"; CI "warm nights" or "temperate nights", and DI "humid". For the winter cycle, however, the DI values were kept high, with the following climate classes: "warm", "temperate warm" and "temperate" for the HI and "very cold nights" for CI.…”
Section: Resultsmentioning
confidence: 99%
“…In São Paulo state, Marin et al (2008) found climate similarities among the wine producing regions of Bento Gonçalves in Rio Grande do Sul, Beli Kriz in Slovenia, Tarragona in Spain, Ajjacio, Bastia, Braga, Bordeaux, Carcassone, Pau and Toulouse in France, Pune, in India, Ravenna in Italy, Kofu in Japan, Napier in New Zealand, Bangkok and Chiangmai in Thailand and Las Brujas in Uruguai. Bardin-Camparotto et al (2014), by using the CCM system to characterize climate potential for grape production in the São Paulo -Circuito das Frutas region, concluded that wine producing climate of the HI class for the summer harvest were "warm", "temperate warm", "temperate"; CI "warm nights" or "temperate nights", and DI "humid". For the winter cycle, however, the DI values were kept high, with the following climate classes: "warm", "temperate warm" and "temperate" for the HI and "very cold nights" for CI.…”
Section: Resultsmentioning
confidence: 99%
“…Atibaia é famosa pelos morangos; Indaiatuba se especializou na produção de uva e acerola; Itatiba se destaca pela produção de caqui; Itupeva destaca-se pela produção de uvas, assim como Louveira e Vinhedo; Morungaba se destaca pela produção de compotas de frutas como uvas, figos, laranjas, pêssegos, entre outras frutas; Valinhos tem alta produção de figos e goiabas, e Jundiaí é referência por sua alta produção de uvas. Segundo Bardin-Camparotto et al (2013), o polo do Circuito das Frutas surgiu nos anos 2000, mas só foi institucionalizado em 2002, pelo Decreto Estadual n. 47.180, sendo comum na região a visitação de turistas a propriedades rurais par a conhecer o processo de produção de frutas, vinhos e doces artesanais, além de haver um calendário de festas que é um atrativo aos visitantes. Os autores notam ainda que a região tem belezas naturais e clima agradável, com potencial para a prática de esportes de aventura, ecoturismo e turismo rural; há ali hotéis, opções de alimentação e comércio variado de frutas e artesanato.…”
Section: Fruticultura Nos Municípios De Itatiba Louveira Valinhos E V...unclassified
“…On the other hand, the sustainability category provides guidelines for the strengthening of viticulture. This fact is based on considering climate change at a global level [90]. Some authors [36] refer that a differentiation must be generated in the sustainable practices of the wineries.…”
Section: Scientific Production Of Wine In the American Continentmentioning
confidence: 99%